P92. Electroencephalographic patterns in different types of status epilepticus – Association with specific syndromes and prognostic significance. Issue 8 (August 2015) - Rösche, J.; Rantsch, K.; Walter, U.; Wittstock, M.; Benecke, R.
<x xml:space="preserve">Abstract</x> Objective It was planned to investigate, whether certain electroencephalographic patterns obtained during the treatment of a status epilepticus (SE) were associated with a particular subtype of SE. Methods In a retrospective databank analysis all treatment episodes of a SE between January 1st 2000 and December 31st 2009 in the department of Neurology of the Universitätsmedizin Rostock were identified. The first EEG of each treatment episode, in which an EEG was recorded, was evaluated. Statistical tests (i.e. chi-square-test and Student t-test) were performed in order to find out whether there is an association of a certain EEG pattern with a particular subtype of SE or whether some EEG patterns signify a worse outcome than others. Results In 35 treatment episodes of a SE at least one EEG was obtained during the actual treatment. There was no association of a certain EEG pattern with a particular subtype of SE. Periodic epileptiform discharges were seen more often in Nonlimbic complex partial status epilepticus and Cases of coma due to acute brain injury with epileptiform EEG changes than in Nonconvulsive status epilepticus (NCSE) in the postictal phase of tonic–clonic seizures. These results are at variance with the published literature, where the frequent occurrence of periodic epileptiform discharges in NCSE in the postictal phase of tonic-clonic seizures is reported. Background slowing with a frequency in the theta-range or lower was associated with disability to perform the activities of daily life without any help. On discharge patients with periodic epileptic discharges were more disabled than those without this pattern. Conclusion The concept of different substypes of NCSE needs further evaluation especially with regard to its therapeutic relevance. In adults EEG patterns specific for a particular subtype of SE are rare.